2023
DOI: 10.3389/fmolb.2023.1082526
|View full text |Cite
|
Sign up to set email alerts
|

Soluble peptidoglycan fragments produced by Limosilactobacillus fermentum with antiproliferative activity are suitable for potential therapeutic development: A preliminary report

Abstract: Currently, the use of probiotic strains and their products represents a promising innovative approach as an antagonist treatment against many human diseases. Previous studies showed that a strain of Limosilactobacillus fermentum (LAC92), previously defined as Lactobacillus fermentum, exhibited a suitable amensalistic property. The present study aimed to purify the active components from LAC92 to evaluate the biological properties of soluble peptidoglycan fragments (SPFs). The cell-free supernatant (CFS) and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 89 publications
0
0
0
Order By: Relevance
“…Overall, we found that putrescine increased the Firmicutes / Bacteroidetes ratio, and a higher Firmicutes/Bacteroidetes ratio is linked to better survival in patients with colorectal cancer ( 51 ). In the phylum Firmicutes , we found an increase in the Limosilactobacillus genus in which Limosilactobacillus fermentum has been reported to produce peptidoglycan with anti-proliferative properties ( 52 ) and Limosilactobacillus reuteri has been shown to suppress colorectal tumorigenesis ( 53 ). Lachnospiraceae are known to produce SCFAs and to play a beneficial role in intestinal health.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we found that putrescine increased the Firmicutes / Bacteroidetes ratio, and a higher Firmicutes/Bacteroidetes ratio is linked to better survival in patients with colorectal cancer ( 51 ). In the phylum Firmicutes , we found an increase in the Limosilactobacillus genus in which Limosilactobacillus fermentum has been reported to produce peptidoglycan with anti-proliferative properties ( 52 ) and Limosilactobacillus reuteri has been shown to suppress colorectal tumorigenesis ( 53 ). Lachnospiraceae are known to produce SCFAs and to play a beneficial role in intestinal health.…”
Section: Discussionmentioning
confidence: 99%
“…gastric and colorectal cancers, and antibiotic-associated diarrhea have all been the subjects of extensive probiotic research [14]. Studies indicate that specific strains of probiotics could alleviate symptoms, reduce inflammation, and restore gut homeostasis in individuals suffering from these conditions.…”
mentioning
confidence: 99%